Discourse on civilization: postliberal postsecular histories of the ghetto - Toffa, Mughammed Sadiq (Social Anthropology, 2025)
This work is a psychoanalytic anthropology of the city in the postcolony. It is located in Europe's most fragile settler colony in the South of Africa, and set within Apartheid's most privileged multi–culture, the Oriental Ghetto of Bo– Kaap, Cape Town. The project introduces the theoretical formulation of ‘Apartheid Orientalism' as the aesthetic classicism of global settler coloniality. Apartheid is the rationalization, industrialization, and massification of colonial relations that condenses world centre and periphery within intimate matrixes of difference that uniquely reveal psychic interiorities (of Self and Other) and material exteriorities (of body and city) as the making of ‘the modern world'. Orientalism dislodges Apartheid from isolation within a normative South African methodological nationalism and peripheral location in the Western Anglo–sphere, toward relocations as avant-garde settler modernism within the global paradigm of settler colonialism and modern world–system analysis. The critical conjugation of ‘Apartheid Orientalism' destabilizes the geohistorical categories within the liberal–secular orthodoxy of both Apartheid historiography as “failed racial state” and Orientalism as “mid–east romance” and reveals the critical conjugation of racial terror and sacred alterity in the modern episteme. Apartheid Orientalism clarifies the order of ‘liberal-secular aesthetics' as the aesthetic idealism of Western Self– and World–making (from Descartes through Kant and Hegel) that gives to the modern the judgment of what is beautiful, right, and good. I confront aesthetic idealism with its Others, the ‘negative' aesthetic of Julia Kristeva and the ‘intransigent' aesthetic of Edward Said, that provide both the coherent figuration of a Master–Subject (‘the designed Self') and the fragmented disfigurations of an Abject–non/Subject (the Native, the Slave, the Oriental). The abject subjectifications of mastery figured in the non-being of ‘Native≠Slave≠Oriental' are ontologically fixed and structurally fragmented within the colonial spheres of the split–off worlds of the Americas, Africa, and Asia. A methodology of ‘boundary–work' and ‘counter–mapping' the city opens a radical phenomenology of colonial mastery: nature mastery binds the Native with the Bantustan complex; technology mastery binds the Slave with the Plantation complex; culture mastery binds the Oriental with the Multiculture complex. The industrial complexes of the modern–colonial episteme produce the National–Tribes (the Eurocentric nation-state) and the Modern–Tribes (the wards of liberal multiculturalism and postmodern identitarian politics). Liberal misrecognition as tribal governance and maintenance reveals the technology of liberal reconciliation. The project calls for the recognition of the sacred and the tragic in modern subjectivity, as the recognition of the postcolony as tragedy. The project offers that the constitution of the ‘immigrant' as Subject in modernity as the global historical conjugation of Native–Slave–Oriental and of postcolonial recognition as ‘immigrant ethics' will bring the postcolony to tragedy and to “a life worth living”.